The Mediating Role of Parental Monitoring Styles in the Relationship Between Internet Addiction and Social Anxiety in Adolescents - Mousavi, Seyedeh Maryam; Mikaeili, Niloofar; Fathi, Aida; Shamifard, Mohadese (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine the mediating role of parental monitoring styles in the relationship between social anxiety and internet addiction among students. Methods and Materials: In terms of purpose, this study was fundamental; in terms of implementation method, it was descriptive; and in terms of design, it was a correlational study using structural equation modeling. The statistical population consisted of students in Zanjan Province during the 2025–2026 academic year. A sample of 220 participants was selected using cluster random sampling. Data were collected using Young’s Internet Addiction Test (Young, 1998), the Small and Kerns Parental Monitoring Styles Questionnaire (Small & Kerns, 1993), and the Social Phobia Inventory (Connor et al., 2000). Data analysis was conducted using structural equation modeling and bootstrap procedures in SPSS version 24 and AMOS version 25. Findings: The model fit indices indicated an acceptable fit. Social anxiety had a positive direct effect on internet addiction (β = 0.42), and parental monitoring styles had a negative direct effect (β = -0.38). The indirect effect of social anxiety through monitoring styles was significant (β = 0.17). Among the monitoring styles, the combined style, as a dynamic approach involving active monitoring, temporary restrictions, and gradual delegation of responsibility, was identified as the most effective approach in reducing internet addiction. Conclusion: Social anxiety leads to increased internet addiction by weakening optimal parental monitoring styles, particularly by reducing combined monitoring. Training parents in the combined monitoring style can disrupt the harmful pathway from social anxiety to digital addiction.